Characterization of Food Waste from a Campus Canteen as Potential Feedstock for Biogas Production - Lieke Riadi; Yunus Fransiscus; Tuani L. Simangunsong; Farida Suhud (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Food waste collected from the Ubaya canteen was characterized for its potential for use as anaerobic feedstock. It was collected for 3 weeks on a daily basis and treated with 2 different pretreatments, i.e. mechanic and mechanic-thermal. The result showed that the physical and chemical properties of the food waste in the 3-week time period of collecting were not significantly different for both pretreatments. The VS/TS ratio was around 96.4% to 97.076% and C/N was in the range of 17.295 to 17.813 for the mechanic and mechanic-thermal treatments. Four semi-batch mesophilic anaerobic digesters were used in this study, with 1.215 gVS/L fed once (R1) and twice daily (R3); 2.43 gVS/L fed once (R2) and twice daily (R4). The maximum methane yield was determined to be 64.61 mL/gVS in R1 after 5 days of incubation and 57.41 mL/gVS in R3 after 4 days of incubation. Systems R2 and R4 showed maximum methane yields of 43.15 mL/gVS and 19.1 mL/gVS respectively.